Efect of Temperature on The Quality of Lemang Using Vertical Type Lemang Cooking - Netty Sinaga; Saipul Bahri Daulay; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The process of lemang cooking is very simple and has some weakness that can be minimalised. The purpose of this research was to examine the effect of temperature in vertical typelemang cooking appliance. This research was carried out at Agricultural Engineering Laboratory, Faculty of Agriculture USU in April – May 2015 using non factorial randomized block design with three levels, i.e. 95oC, 100oC, and 105oC. Parameters observed were effective capacity and organoleptic values. The results showed that cooking temperature had significant effect on the organoleptic test. But had no significant effect on  the effective capacityof the appliance. Keywords: Glutinous rice, Lemang’s, glutinous rice cooker appliance.